Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Pembentukan Karakter Peserta Didik di Sekolah Dasar - Bhughe, Kristina Intani (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2022)
AbstractThis study aims to determine the role of Pancasila and Citizenship Education teachers in shaping the character of the Inpres Hale Elementary School students, as well as the challenges and obstacles faced by Pancasila and Citizenship Education teachers in shaping the character of the Hale Inpres Elementary School students. This study used qualitative research methods. The survey respondents were the Principal of Inpres Hale Elementary School, Pancasila and Citizenship Education Teachers, Class VI guardians, parents, students and the community. Data collection techniques through observation, interviews and documentation. Data analysis through data collection, data reduction, conclusion or verification. The results showed Pancasila and Citizenship Education teachers’ role was to embody the value of positive attitudes towards students, such as being polite, and punctual, dressing according to school rules and providing guidance and advice. Non-compliance with school rules, tardiness and truancy, and the influence of school, family, and environmental factors. —————AbstrakPenelitian ini bertujuan untuk mengetahui peran guru Pendidikan Pancasila dan Kewarganegaraan (PPKn) dalam membentuk karakter siswa di Sekolah Dasar Inpres Hale, serta tantangan dan hambatan yang dihadapi guru PPKn dalam membentuk karakter Siswa Sekolah Dasar Inpres Hale. Penelitian ini menggunakan metode penelitian kualitatif. Responden survei adalah Kepala Sekolah Dasar Inpres Hale, Guru PPKn, wali kelas VI, orang tua, peserta didik dan masyarakat. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Analisis data melalui pengumpulan data, reduksi data, kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa peran guru PPKn adalah mewujudkan nilai sikap positif terhadap siswa, seperti bersikap sopan, tepat waktu, berpakaian sesuai aturan sekolah dan memberikan bimbingan dan nasehat.Tantangan dan hambatan yang dihadapi guru PPKn dalam membentuk karakter siswa sekolah dasar Inpres Hale adalah ketidakpatuhan terhadap peraturan sekolah, keterlambatan dan tindakan membolos, serta pengaruh faktor sekolah, keluarga, dan lingkungan.